Effects of Leg Motor Imagery Combined With Electrical Stimulation on Plasticity of Corticospinal Excitability and Spinal Reciprocal Inhibition - Takahashi, Yoko; Kawakami, Michiyuki; Yamaguchi, Tomofumi; Idogawa, Yusuke; Tanabe, Shigeo; Kondo, Kunitsugu; Liu, Meigen (Frontiers in Neuroscience, 2019)
Motor imagery (MI) combined with electrical stimulation (ES) enhances upper-limb corticospinal excitability. However, its after-effects on both lower limb corticospinal excitability and spinal reciprocal inhibition remain unknown. We aimed to investigate the effects of MI combined with peripheral nerve ES (MI + ES) on the plasticity of lower limb corticospinal excitability and spinal reciprocal inhibition. Seventeen healthy individuals performed the following three tasks on different days, in a random order: 1) MI alone; 2) ES alone; and 3) MI + ES. The MI task consisted of repetitive right ankle dorsiflexion for 20 min. ES was percutaneously applied to the common peroneal nerve at a frequency of 100 Hz and intensity of 120% of the sensory threshold of the tibialis anterior (TA) muscle. We examined changes in motor-evoked potential (MEP) of the TA (task-related muscle) and soleus muscle (SOL; task-unrelated muscle). We also examined disynaptic reciprocal inhibition before, immediately after, and 10, 20, and 30 min after the task. MI + ES significantly increased TA MEPs immediately and 10 min after the task compared with baseline, but did not change the task-unrelated muscle (SOL) MEPs. MI + ES resulted in a significant increase in the magnitude of reciprocal inhibition immediately and 10 min after the task compared with baseline. MI and ES alone did not affect TA MEPs or reciprocal inhibition. MI combined with ES is effective in inducing plastic changes in lower limb corticospinal excitability and reciprocal Ia inhibition.